Time-Integrated Searches for Point-like Sources of Neutrinos with the 40-String IceCube Detector - Collaboration, TI; Abbasi, R (Institute of Physics Publishing, 2010)
We present the results of time-integrated searches for astrophysical neutrino sources in both the northern and southern skies. Data were collected using the partially-completed IceCube detector in the 40-string configuration between 2008 April 5 and 2009 May 20, totaling 375.5 days livetime. An unbinned maximum likelihood ratio method is used to search for astrophysical signals. The data sample contains 36,900 events: 14,121 from the northern sky, mostly muons induced by atmospheric neutrinos and 22,779 from the southern sky, mostly high energy atmospheric muons. The analysis includes searches for individual point sources and targeted searches for specific stacked source classes and spatially extended sources. While this analysis is sensitive to TeV-PeV energy neutrinos in the northern sky, it is primarily sensitive to neutrinos with energy greater than about 1 PeV in the southern sky. No evidence for a signal is found in any of the searches. Limits are set for neutrino fluxes from astrophysical sources over the entire sky and compared to predictions. The sensitivity is at least a factor of two better than previous searches (depending on declination), with 90% confidence level muon neutrino flux upper limits being between E^2 dN/dE ~ 2 - 200 × 10^-12 TeV cm^-2 s^-1 in the northern sky and between 3 -700 × 10^-12 TeV cm^-2 s^-1 in the southern sky. The stacked source searches provide the best limits to specific source classes. The full IceCube detector is expected to improve the sensitivity to E^-2 sources by another factor of two in the first year of operation.